Genomic analysis of recurrences and high‐grade forms of polymorphous adenocarcinoma. Issue 2 (18th June 2019) - Sebastiao, Ana P M; Pareja, Fresia; Kumar, Rahul; Brown, David N; Silveira, Catarina; da Silva, Edaise M; Lee, Ju Y; Del, Angela; Katabi, Nora; Chiosea, Simion; Weigelt, Britta; Reis‐Filho, Jorge S; et al.
Abstract : Aims: Polymorphous adenocarcinoma (PAC) usually follows an indolent course, but some cases may show recurrences and high‐grade features. The genetic events associated with recurrences and high‐grade versions are yet to be defined. Our aim was to determine the genetic underpinning of recurrent PACs of the salivary gland and the repertoire of somatic genetic alterations in cases with high‐grade histology. Methods and results: Four PACs from three patients, including one case with matching primary and recurrent tumours, one de‐novo high‐grade PAC, and a PAC that transformed to a high‐grade tumour following multiple recurrences, were subjected to targeted sequencing (Memorial Sloan Kettering Mutation Profiling of Actionable Cancer Targets assay) or whole‐exome sequencing. Both matching primary and recurrent tumours, and the de‐novo high‐grade PAC, harboured clonal PRKD1 E710D hotspot mutations, whereas the PAC that underwent high‐grade transformation upon recurrence, which was wild‐type for PRKD1, harboured a PRKD2 rearrangement. The PACs analysed here also harboured mutations targeting cancer genes such as PIK3CA, SETD2, ARID1A, and NOTCH2 . A clonal decomposition analysis of the matching primary and recurrent PACs revealed that a minor subclone from the primary tumour became dominant in the recurrent tumour following a clonal selection evolutionary pattern. Conclusions: Our findings demonstrate that recurrent and high‐grade PACs are underpinned by PRKD1 E710D hotspot mutations or PRKD2 rearrangements, and that recurrences of PACs may stem from the selection of pre‐existing subclones in the primary tumour.